MENINGKATKAN AKTIVITAS DAN KREATIVITAS SISWA PADA MUATAN IPA MENGGUNAKAN MODEL BINTANG DI SEKOLAH DASAR - Rifka Zuhairiah, Aliza; Riandy Agusta, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this research is the low level of student activity and creativity in science learning. The solution to overcome this problem is to use the BINTANG model, which is implemented in the learning process. This research uses a type of classroom action research (CAR) with the approach in this research being quantitative and qualitative. The research results showed that teacher activity obtained a percentage of 95% with the criteria "very good", student activity obtained a percentage of 92% with the criterion "very active", student creativity obtained a percentage of 92% with the criteria "very creative" and learning outcomes obtained a percentage of 100 % with the criteria "complete". Based on the data and research results, it can be concluded that the application of the BINTANG model (Creative Problem Solving, Picture and Picture, and Teams Games Tournament) can increase creativity and have a very good impact on improving student learning outcomes.